Autophagosome maturation: An epic journey from the ER to lysosomes - Zhao, Yan G.; Zhang, Hong (The Journal of cell biology, 2019)
Macroautophagy involves the sequestration of cytoplasmic contents in a double-membrane autophagosome and their delivery to lysosomes for degradation. In multicellular organisms, nascent autophagosomes fuse with vesicles originating from endolysosomal compartments before forming degradative autolysosomes, a process known as autophagosome maturation. ATG8 family members, tethering factors, Rab GTPases, and SNARE proteins act coordinately to mediate fusion of autophagosomes with endolysosomal vesicles. The machinery mediating autophagosome maturation is under spatiotemporal control and provides regulatory nodes to integrate nutrient availability with autophagy activity. Dysfunction of autophagosome maturation is associated with various human diseases, including neurodegenerative diseases, Vici syndrome, cancer, and lysosomal storage disorders. Understanding the molecular mechanisms underlying autophagosome maturation will provide new insights into the pathogenesis and treatment of these diseases.